Some Edible Insect Species Consumed by the People of Benue State, Nigeria - Agbidye, F.S.; Ofuya, T.I.; Akindele, S.O. (Pakistan Journal of Nutrition, 2009)
The study surveyed the edible insect species consumed by the people of Benue State, Nigeria and also identified the most abundant, most preferred and most consumed edible insect species in the study area. Seven hundred and eighty (780) copies of questionnaire were administered in 10 out of the 23 Local Government Areas and 3 major towns of Benue State. The frequencies generated from the questionnaire were transformed and subjected to one-way ANOVA. The termite, Macrotermes natalensis Haviland (253±92.3), was the most prevalent followed by the large African cricket, Brachytrupes membranaceus Drury (252±95.9) while the pallid emperor moth, Cirina forda Westwood (185±66.7) came third. There were however, no significant differences in the mean frequencies of these three edible insects above (p<0.05). Other edible insect species encountered included Rhynchophorus phoenicis, Zonocerus variegatus L., Oryctes monocerus Olivier Gryllotalpa africana P.de.B. Bunaea alcinoe Cram, Nezara viridula L. and Heteroligus meles Billberger. The most abundant, most preferred and most consumed edible insect species was Macrotermes natalensis followed by Brachytrupes membranaceus and then Cirina forda. In all cases, the result of one-way ANOVA showed no significant differences among these three insect species (p<0.05).